On ENSO impacts on European wintertime rainfalls and their modulation by the NAO and the Pacific multi-decadal variability described through the PDO index - Zanchettin, D; Franks, SW; Traverso, P; Tomasino, M (2008)
While strong relationships have previously been established between the El Ni˜no/Southern Oscillation (ENSO) and climate variability in many parts of the world, previous analyses of ENSO impacts on European rainfalls have been variable and inconclusive. In this paper, the role and apparent interactions of a range of known teleconnections are assessed. It is shown that ENSO events do indeed appear to impact European rainfalls and that these impacts are likely to also depend on the concurrent state of the North Atlantic Oscillation (NAO) and the Pacific Decadal Oscillation (PDO). In particular, it is demonstrated that ENSO impacts most significantly on European wintertime rainfalls during positive (warm) phases of the PDO.